Biocompatible and biodegradable inorganic nanostructures for nanomedicine: Silicon and black phosphorus. (April 2019) - Qiu, Meng; Singh, Ajay; Wang, Dou; Qu, Junle; Swihart, Mark; Zhang, Han; Prasad, Paras N.
Graphical abstract: Highlights: The significance of silicon and black phosphorus nanomaterials in biomedical science is introduced. Fabrication, surface functionalization and properties of silicon and black phosphorus nanomaterials are addressed. Toxicity, biodistribution, elimination and bioavailability of silicon and black phosphorus nanomaterials are reviewed. Biomedical applications such as bioimaging, biosensing, nano-therapy and theraostics are discussed. Perspectives on the challenges and future prospects of silicon and black phosphorus nanomaterials are provided. Abstract: Nanomedicine has made great progress toward the diagnosis and treatment of diseases by exploiting physicochemical properties and biological interactions of nanomaterials that differ from the corresponding conventional materials. In the past decade, the advancement of biocompatible and biodegradable inorganic nanostructures has produced numerous nanomedicine platforms. Silicon and, more recently, black phosphorus (BP) offer promising nanoplatforms for bio-applications, including bioimaging, photo-therapy, drug delivery, combination therapy, and theranostics, due to their intrinsic unique properties, negligible elemental cytotoxicity, high drug-loading potential, long blood circulation time, and specific clearance pathways. In view of the growing importance of silicon and BP nanomaterials in the progress of nanomedicine, and their common feature characteristics as biodegradable biocompatible elemental semiconductors, this contribution reviews the latest advances in silicon and BP-based biomedical nanomaterials for disease diagnosis and therapy.